First record and supplementary description of Leporinus amae Godoy, 1980 (Characiformes: Anostomidae) from freshwaters in Argentina - Almirón, Adriana Edith (2013)
Leporinus amae is known from the Rio Apuaê (type locality), Rio Canoas and Rio Caveiras tributaries of the Uruguay River basin, in Brazil. The original description of this species was mainly based on a single specimen lacking intraspecific variation in meristic and morphometric of most characters. We expand the range of distribution and report the first occurrence of Leporinus amae in Misiones Province, Argentina. Additionally, we provide a supplementary description of the species.